A new species of Catopsis (Bromeliaceae, Tillandsioideae, Catopsideae) of Mexico - Martínez-Correa, Nancy; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2014)
Catopsis occulta Mart.-Correa, Espejo & López-Ferr., a new endemic species from the states of Chiapas, Oaxaca and Veracruz in Mexico, is described and illustrated. The new taxon is characterized by dioecious, large plants with usually three times branched inflorescences and yellow-orange floral bracts and sepals. The new species is compared with C. berteroniana (Schult. & Schult. f.) Mez, which is morphologically similar.